High School Students' Mathematical Connection Ability Profile in Solving Three-Variable Linear Equation System Problems Based on Cognitive Style - Maria Densiana Nailake; Aloisius Loka Son; Eduardus Beo Seso Delvion (CV. Samuel Manurung and Co, 2023)
This study aims to describe the profile of high school students' mathematical connection abilities in solving problems on systems of three-variable linear equations based on cognitive style. The method used in this research is qualitative. This research was carried out in the even semester of the 2022/2023 academic year. The research subjects were 27 class X students at a high school in the North Central Timor district. Subjects were grouped based on FI and FD cognitive styles. Next, 6 subjects were selected, namely 3 FI and 3 FD to take the mathematical connection ability test. The instruments used in this research were GEFT, mathematical connection ability tests, and interviews. Data analysis techniques are data reduction, data presentation, and conclusion. The results of this study show that the mathematical connection abilities of each student are different. Subjects with a field-independent cognitive style meet all indicators of mathematical connection ability, while subjects with a field-dependent cognitive style do not meet all indicators of mathematical connection ability